Endoscopic hemostasis state of the art - Nonvariceal bleeding - Goelder, Stefan Karl (World J Gastrointest Endosc, 2016)
New endoscopic techniques for hemostasis in nonvariceal bleeding were introduced and known methods further improved. Hemospray and Endoclot are two new compounds for topical treatment of bleeding. Initial studies in this area have shown a good hemostatic effect, especially in active large scale oozing bleeding, e.g., tumor bleedings. For further evaluation larger prospective studies comparing the substanced with other methods of endoscopic hemostasis are needed. For localized active arterial bleeding primary injection therapy in the area of ​​bleeding as well as in the four adjacent quadrants offers a good method to reduce bleeding activity. The injection is technically easy to learn and practicable. After bleeding activity is reduced the bleeding source can be localized more clearly for clip application. Today many different through-the-scope (TTS) clips are available. The ability to close and reopen a clip can aid towards good positioning at the bleeding site. Even more important is the rotatability of a clip before application. Often multiple TTS clips are required for secure closure of a bleeding vessel. One model has the ability to use three clips in series without changing the applicator. Severe arterial bleeding from vessels larger than 2 mm is often unmanageable with these conventional methods. Here is the over-the-scope-clip system another newly available method. It is similar to the ligation of esophageal varices and involves aspiration of tissue into a transparent cap before closure of the clip. Thus a greater vascular occlusion pressure can be achieved and larger vessels can be treated endoscopically. Patients with severe arterial bleeding from the upper gastrointestinal tract have a very high rate of recurrence after initial endoscopic treatment. These patients should always be managed in an interdisciplinary team of interventional radiologist and surgeons.